Adipogenic Impairment of Adipose Tissue-Derived Mesenchymal Stem Cells in Subjects With Metabolic Syndrome: Possible Protective Role of FGF2 - Oliva Olivera, Wilfredo; Coín-Aragüez, Leticia I.; Lhamyani, Said; Clemente-Postigo, María Mercedes; Alcaide Torres, Juan; Bernal-López, María Rosa; El-Bekay, Rajaa; Tinahones-Madueño, Francisco José (Endocrine Society, 2017)
Context: The decreased expansion capacity of adipose tissue plays a crucial role in the onset of disorders associated with metabolic syndrome. Objetive: The aim of this study was to examine the state of adipose tissue-derived mesenchymal stem cells (ASCs) from obese subjects with different metabolic profiles. Design: This was a 2-year study to enroll subjects who underwent bariatric surgery or cholecystectomy. Setting: University Hospital Patients and Intervention: Patients who underwent either bariatric surgery (20 morbidly obese) or cholecystectomy (40 subjects) participated in the study. Main Outcome Measures: ASCs were obtained from both visceral and subcutaneous adipose tissue. Adipogenic, fibrotic genes expression was quantified by qPCR; Smad7 and fibroblast growth factor 2 (FGF2) were quantified by western blotting and ELISA respectively. The susceptibility of ASCs to apoptosis, their population doubling time and clonogenic potential were evaluated Results The worsening metabolic profile of the subjects was accompanied by a decrease in the intrinsic levels of adipogenic genes expression, reduced proliferation rate, clonogenic potential and exportation of FGF2 to the cell surface of the ASCs derived from both tissues. In addition, the ASCs from NonMS subjects showed differences in susceptibility to apoptosis and expression of TGFß signaling inhibitory protein Smad7 with respect to the ASCs from MS subjects. Conclusions/Interpretation Our results suggest that the decrease in adipogenic genes mRNA and clonogenic potential as well as the accumulation of fibrotic proteins with metabolic alterations could be a relevant mechanism controlling the number and size of neogenerated adipocytes and involved in adipose tissue expansion alteration.
Keywords: Síndrome metabólico; Tejido adiposo; Obesidad; Obesity; Adipose tissue; Adipose Tissue-Derived Mesenchymal Stem Cells; Metabolic Syndrome; FGF2